Immediate remote ischemic postconditioning reduces cerebral damage in ischemic stroke mice by enhancing leptomeningeal collateral circulation. Issue 8 (10th December 2018) - Zhang, Ying; Ma, Longhui; Ren, Changhong; Liu, Kaiyin; Tian, Xin; Wu, Di; Ding, Yuchuan; Li, Junfa; Borlongan, Cesar V.; Ji, Xunming
Abstract: Remote ischemic postconditioning (RIPC) is a promising neuroprotective strategy for ischemic stroke. Here, we employed a focal ischemic stroke mouse model to test the hypothesis that poststroke collateral circulation as a potent mechanism of action underlying the therapeutic effects of immediate RIPC. During reperfusion of cerebral ischemia, the mice were randomly assigned to receive RIPC, granulocyte colony‐stimulating factor (G‐CSF) as a positive control, or no treatment. At 24 hr, we found RIPC and G‐CSF increased monocytes/macrophages in the dorsal brain surface and in the spleen, coupled with enhanced leptomeningeal collateral flow compared with nontreatment group. Blood monocytes depletion by 5‐fluorouracil (5‐FU) significantly limited the neuroprotection of RIPC or G‐CSF treatment. The protein expression of proangiogenic factors such as Ang‐2 was increased by ischemia, but treatment with either RIPC or G‐CSF showed no further upregulation. Thus, immediate RIPC confers neuroprotection, in part, by enhancing leptomeningeal collateral circulation in a mouse model of ischemic stroke. Abstract : Remote ischemic postconditioning (RIPC) is a promising neuroprotective strategy for ischemic stroke. Deep understanding the mechanism through which remote ischemic conditioning (RIC) exerts its powerful function may facilitate its clinical application for ischemic stroke patients. Our present study showed that immediate RIPC reduced cerebral damage by leptomeningeal collateral flow augmentation via spleen‐derived monocytes/macrophages recruitment in ischemic stroke mice.